Reconstitution of cytomegalovirus‐specific T‐cell response in allogeneic hematopoietic stem cell recipients: the contribution of six frequently recognized, virus‐encoded ORFs. Issue 3 (9th June 2016) - Nemeckova, S.; Krystofova, J.; Babiarova, K.; Hainz, P.; Musil, J.; Sroller, V.; Maly, M.; Stastna‐Markova, M.
Abstract: Background: The reactivation of human cytomegalovirus (HCMV) in immunosuppressed patients is associated with significant morbidity. Testing HCMV‐specific T‐cell responses can help determine which patients are at high risk of HCMV disease. We optimized selection of HCMV antigens for detection of T‐cell response of patients after allogeneic hematopoietic stem cell transplantation (HSCT) with the aim of identifying patients with insufficient control of HCMV reactivation. Methods: T‐cell immune response to HCMV was monitored in 30 patients during the first year after HSCT. The HSCT recipients were classified according to their anti‐HCMV T‐cell response and the presence of HCMV DNA in the blood. Results: We observed an inverse relationship between the magnitude of HCMV‐specific T‐cell responses against CMV lysate, phosphoprotein (pp) 65, immediate early‐1 (IE‐1), UL36, and UL55, but not to US3 and US29 detected by interferon‐gamma (IFNγ)‐ ELISPOT and the level of HCMV DNA in the blood of patients during the 30 days following sampling. The study has revealed that patients who received a graft from a seronegative donor have a lower T‐cell response against HCMV and increased probability of HCMV reactivation in comparison to the patients who had received their graft from a seropositive donor. Conclusion: The individual peptide pools and native HCMV antigens were useful for monitoring the time course of the anti‐HCMV response by IFNγ‐ELISPOT, which proved to have a prognostic value. Besides widely employed peptide pools of pp65 and IE‐1, the use of antigens UL36 and UL55, but not US3 or US29, increased sensitivity of the test.